Noninvasive assessment of intracranial elastance and pressure in spontaneous intracranial hypotension by MRI. Issue 5 (13th February 2018) - Tsai, Yi‐Hsin; Chen, Hung‐Chieh; Tung, Hsin; Wu, Yi‐Ying; Chen, Hsian‐Min; Pan, Kuan‐Jung; Cheng, Da‐Chuan; Chen, Jeon‐Hor; Chen, Clayton Chi‐Chang; Chai, Jyh‐Wen; Shen, Wu‐Chung
Abstract : Background: Spontaneous intracranial hypotension (SIH) is often misdiagnosed, and can lead to severe complications. Conventional MR sequences show a limited ability to aid in this diagnosis. MR‐based intracranial pressure (MR‐ICP) may be able to detect changes of intracranial elastance and pressure. Purpose: To determine whether MR‐ICP is able to differentiate SIH patients from normal subjects, improve diagnostic sensitivity, and provide an insight into the pathophysiology. Study Type: Prospective. Subjects: Twenty‐eight SIH cases with orthostatic headache and 20 healthy volunteers. Field Strength/Sequence: Cine phase‐contrast MRI on a 1.5T scanner. Assessment: Intracranial elastance (IE) was derived from the ratio of the peak‐to‐peak cerebrospinal fluid (CSF) pressure gradient (PGcsf‐pp ) and intracranial volume change, obtained by summing all flows before each sequential cardiac frame. Statistical Tests: Student's t ‐test was used to compare the MR‐ICP indexes and flow parameters between SIH patients and healthy volunteers ( P < 0.01). Results: The SIH patients with cervical epidural venous dilatation (EVD) had an IE of 0.121 ± 0.027 mmHg/cm/ml, significantly higher than that of the normal volunteers (0.085 ± 0.027 mmHg/cm/ml; P = 0.002). In contradistinction, the EVD‐negative SIH patients, including four with no sign of CSF leaks, had significantly lower IE (0.055 ± 0.012 mmHg/cm/ml) compared with the normal volunteers and the EVD‐positive group ( P = 0.001, P < 0.001). The EVD‐negative patients had significantly lower PGcsf‐pp (0.024 ± 0.007 mmHg/cm) compared with the normal volunteers and the EVD‐positive group (0.035 ± 0.011 mmHg/cm, 0.040 ± 0.010 mmHg/cm; P = 0.003, P < 0.001). Additionally, the MRI flow study showed a significant decrease in transcranial inflow and outflow of SIH patients ( P < 0.01). Data Conclusion: We found that the MR‐ICP method is potentially more sensitive than morphological MRI in the early diagnosis of SIH. Also, contrary to common belief, our results suggest that an abnormal craniospinal elastance might be the cause of SIH, instead of CSF leak. Level of Evidence : 2 Technical Efficacy : Stage 3 J. Magn. Reson. Imaging 2018;47:1255–1263.